Preparation method of high-strength and high-wear-resistant boron nitride reinforced copper-based composite material
Through molecular-level mixing technology and vacuum smelting combined with hot processing deformation treatment, boron nitride-reinforced copper-based composite materials were prepared, solving the dispersion and interface bonding of BNNS in the copper matrix, and achieving the comprehensive performance improvement of high strength, high wear resistance and good conductivity.
Patent Information
- Application Number
- CN202310576286.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-22
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-05-22
AI Technical Summary
The prior art is difficult to achieve uniform dispersion and structural integrity of boron nitride nanosheets (BNNS) in copper matrix, while maintaining good interfacial bonding strength, resulting in a degradation of composite properties.
The BNNS@Cu composite reinforcement was prepared by molecular horizontal mixing process (MLM), and then mixed with trace nanoTi powder and obtained the BNNS@Cu-(Ti) composite powder by low-energy ball milling. It was then uniformly mixed with the Cu melt in a vacuum induction melting furnace. After cooling, it was subjected to hot processing and deformation treatment to generate an interface transition layer to improve interface bonding.
The uniform dispersion of BNNS in the copper matrix is achieved, structural integrity is maintained, and the interface bonding strength between BNNS and the copper matrix is significantly improved, the mechanical properties and wear resistance of the composite material are improved, while maintaining good conductivity.
Smart Images

Figure CN116607043B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and specifically relates to a method for preparing a novel high-strength and high-wear-resistant boron nitride reinforced copper-based composite material. Background Art
[0002] Copper has excellent electrical and thermal conductivity and ductility, and is widely used in power transmission cables, tram contact switches, brushes, integrated circuit leads and other fields. Since the discovery of two-dimensional boron nitride nanosheets (BNNS), it has attracted widespread attention in the field of nanomaterials due to its excellent mechanical and physical and chemical properties. Compared with graphene, in addition to excellent mechanical properties, BNNS also has excellent properties such as high temperature resistance, high thermal conductivity, stronger chemical corrosion resistance, and good self-lubrication (friction coefficient <0.16), making it more promising than graphene in many aspects. Therefore, the use of BNNS as a reinforcing phase provides a new opportunity for the development of high-strength and high-wear-resistant copper-based composites.
[0003] At present, mechanical ball milling or in-situ autogenous method is commonly used to prepare BNNS reinforced copper-based composites. Mechanical ball milling is a simple and low-cost method that is an efficient preparation method. However, in order to achieve uniform dispersion of the reinforcement phase, ultra-high-speed ball milling often destroys the reinforcement phase structure (high defect rate) and cannot effectively exert the intrinsic strengthening effect of the reinforcement. The in-situ autogenous method generates a particle reinforcement phase by in-situ reaction inside the copper matrix. Although it can solve the problems of poor interface bonding and particle surface contamination of traditional copper-based composites, if the synthesized particle reinforcement phase (TiB x ) If the volume fraction is too high, it is easy to aggregate at the grain boundary and produce a large number of defects, which reduces the interface bonding of BNNS-Cu and leads to a serious decline in the performance of the composite material. Up to now, there is still a lack of effective preparation methods for the preparation of high-performance BNNS reinforced copper-based composites. How to achieve uniform dispersion of BNNS, ensure its structural integrity, and maintain good interface bonding strength is still a key scientific problem that needs to be solved urgently. Summary of the invention
[0004] Based on the above research background, the present invention proposes a method for preparing a new type of high-strength and high-wear-resistant boron nitride reinforced copper-based composite material. The method first adopts a molecular level mixing process (MLM) to prepare a BNNS@Cu composite reinforcement, and then mixes it with a trace amount of nano-Ti powder and obtains a BNNS@Cu-(Ti) composite powder by low-energy ball milling. The above composite powder is uniformly mixed with the Cu melt in a vacuum induction melting furnace, and a BNNS@Cu-(Ti) / Cu composite block is obtained after cooling. Finally, the composite block is subjected to hot working deformation (hot rolling) treatment to obtain a BNNS@Cu-(Ti) / Cu composite material. On the one hand, this preparation method can reduce the density difference between BNNS and the copper matrix and realize the uniform dispersion of BNNS in the copper matrix; on the other hand, the addition of Ti can improve the wettability between BNNS and the copper matrix (reduce the wetting angle) and strengthen the interface bonding of BNNS-Cu. The preparation process is simple and practical, and can effectively solve the problems in the background technology. The prepared copper-based composite material exhibits excellent mechanical properties and wear resistance, and still maintains good electrical conductivity, providing technical guidance for the development of high-performance copper-based composite materials for use in brush materials, pantograph slide materials, electrical contact materials and friction materials.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A method for preparing a novel high-strength and high-wear-resistant boron nitride reinforced copper-based composite material, the steps of which are as follows:
[0007] (1) Preparation of Boron Nitride Nanosheets Reinforced Copper Matrix (BNNS@Cu) Composite Reinforcements
[0008] 0.3g to 3g of boron nitride nanosheet (BNNS) powder and 15g to 150g of hydrated copper acetate (CuAc·H2O) were weighed and ultrasonically dispersed in deionized water for 10min to 20min respectively for later use. The BNNS dispersion solution was added to the CuAc·H2O solution and stirred in a water bath at 60℃ to 80℃ for 30min to 60min to obtain a BNNS / CuAc mixed solution. Subsequently, 9g to 90g of sodium hydroxide (0.5mol / L) and 7g to 70g of glucose (0.8mol / L) were weighed and dispersed into a solution and then added to the above mixed solution in sequence. When the color of the solution changes from dark blue to brick red, stirring was stopped, and BNNS / CuO powder was obtained by filtration and vacuum drying. Finally, the above powder was reduced in a vacuum tube furnace with Ar / H2 as protective reducing gas at a certain temperature for a period of time to obtain BNNS@Cu composite reinforcement powder. The reaction principle is shown as (1)(2)(3)(4):
[0009] Cu(Ac)2·H2O + 2NaOH → Cu(OH)2↓ + 2NaAc+ H2O (1)
[0010] Cu(OH)2 → CuO↓ + H2O (2)
[0011] 2CuO + C6H 12 O6 + NaOH → Cu2O↓ + C6H 11 O7Na + H2O (3)
[0012] Cu2O + H2 → 2Cu + H2O (4)
[0013] (2) Preparation of BNNS@Cu-(Ti) composite powder
[0014] The BNNS@Cu powder obtained in step (1) and 1 g to 10 g of nano-Ti powder are mixed in a ball mill, and alcohol is added, and argon is used as a protective gas. After ball milling for 120 min to 180 min, the powder is vacuum dried to obtain BNNS@Cu-(Ti) flaky composite powder (flaky powder has a large specific surface area and can effectively improve the interface bonding between BNNS and copper substrate).
[0015] (3) Preparation of BNNS@Cu-(Ti) / Cu composite bulk
[0016] Weigh 30 g to 300 g of Cu powder and melt it into a Cu melt at 1100° C. to 1300° C. in a vacuum induction melting furnace. Add the BNNS@Cu-(Ti) composite powder obtained in step (2), evacuate the furnace to a vacuum (with Ar as the protective gas), continue melting at 1100° C. to 1300° C., and repeat the melting for 3 to 5 times (stirring / turning the sample 3 to 5 times) until it is evenly mixed to ensure that the sample is completely melted to the bottom surface of the mold. After keeping warm for 5 min to 10 min, turn off the vacuum, turn off the instrument, and take out the sample after the melt solidifies and the cavity cools to room temperature (about 20 min) to obtain a BNNS@Cu-(Ti) / Cu composite block.
[0017] (4) Thermal deformation
[0018] The BNNS@Cu-(Ti) / Cu composite block obtained in step (3) is subjected to heat deformation treatment in a high temperature environment of 800°C to 1000°C using a hot working deformation equipment (hot rolling mill) to eliminate the micropores generated by smelting and obtain a denser BNNS@Cu-(Ti) / Cu composite material.
[0019] Preferably, the proportion of BNNS powder in step (1) is: 0.1wt% to 0.3wt% (calculated by total amount); the sheet diameter is 100nm to 200nm; the morphology can be a single-layer, double-layer or multi-layer structure of boron nitride nanosheets.
[0020] Preferably, in step (1), CuAc·H2O is of analytical grade (AR≥99%); NaOH is of analytical grade (AR≥99%); and glucose is of analytical grade (AR≥99%).
[0021] Preferably, the vacuum drying in step (1) adopts a vacuum rotary evaporation device, and its rotation speed is ≤60r / min.
[0022] Preferably, in step (1), the vacuum tube furnace has a heating rate of 5°C / min to 10°C / min, a holding temperature of 300°C to 400°C, and a holding time of 200min to 300min.
[0023] Preferably, in step (2), the particle size of the Ti powder is 100 nm to 200 nm; the morphology is spherical; and the addition amount is 1 wt% to 3 wt% (calculated based on the total amount).
[0024] Preferably, in step (2), the amount of alcohol added is 1 / 4 to 1 / 3 of the volume of the ball mill; the ball-to-material ratio is 10:1 to 15:1; and the ball mill speed is 200 r / min to 250 r / min.
[0025] Preferably, in step (2), vacuum drying is performed using a vacuum rotary evaporation device, and the rotation speed thereof is ≤60 r / min.
[0026] Preferably, in step (3), the particle size of the Cu powder is 20 μm to 50 μm; the morphology can be spherical, flaky, or any irregular shape.
[0027] Preferably, in step (3), the initial vacuum degree of the vacuum induction melting furnace is: 5×10 -4 ~10 -3 Pa; heating rate: 50℃ / min~100℃ / min.
[0028] Preferably, the step (4) is hot-rolled for 3 to 5 times, with the pressing amount of each time being ≤2 mm, the rolling deformation being ≤30%; and the total rolling deformation being ≤90%.
[0029] Beneficial effects of the present invention:
[0030] (1) The method for preparing the boron nitride reinforced copper-based composite material of the present invention, on the one hand, the BNNS@Cu composite reinforcement prepared by the MLM method can reduce the density difference between the low-density BNNS and the copper matrix, and realize the uniform dispersion of BNNS in the copper matrix; on the other hand, the vacuum melting technology combined with the hot working deformation can generate TiB by in-situ interface reaction. x The transition layer improves the interface bonding between the copper matrix and BNNS, ensuring and improving the performance of the composite material.
[0031] (2) Compared with traditional copper-based composite materials reinforced with particles or low-dimensional carbon materials, the BNNS / Cu composite materials prepared in the present invention can maintain good electrical conductivity while obtaining excellent mechanical properties and wear resistance, thus achieving the successful development of copper-based composite materials with high comprehensive performance.
[0032] (3) The preparation method of the present invention has a short cycle and strong practicality, and provides technical guidance for the research and development of high-performance copper-based composite materials for application in the field of power electronic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced and explained below.
[0034] Figure 1 This is a scanning electron microscope image (SEM) of the BNNS@Cu-(Ti) powder after ball milling in step (2) of Example 1;
[0035] Figure 2 This is an electron probe microscopy (EPMA) surface scanning image of the BNNS@Cu-(Ti) / Cu composite material after being deformed by high-temperature heat processing at 800°C in step (4) of Example 1;
[0036] Figure 3 The bar graphs are the conductivity and hardness change of BNNSs@Cu-(Ti) / Cu and BNNS / Cu composite materials after 800°C high temperature hot working deformation in Example 1 and Comparative Example 1;
[0037] Figure 4 The stress-strain curves and the friction coefficient change curves of the BNNS@Cu-(Ti) / Cu and BNNS / Cu composite materials after 800°C high temperature hot working deformation in Example 1 and Comparative Example 1;
[0038] Figure 5 The bar graphs are the conductivity and hardness change of BNNS@Cu-(Ti) / Cu and BNNS / Cu composite materials after 1000°C high temperature hot working deformation in Example 2 and Comparative Example 2;
[0039] Figure 6 These are the stress-strain curves and friction coefficient change curves of the BNNS@Cu-(Ti) / Cu and BNNS / Cu composite materials after high-temperature hot working deformation at 1000°C in Example 2 and Comparative Example 2.
[0040] Figure 7 The bar graphs of the conductivity and hardness changes of BNNS@Cu-(Ti) / Cu and BNNS / Cu composite materials after 1000°C high temperature hot working deformation in Example 3 and Comparative Example 3 are shown;
[0041] Figure 8 The stress-strain curves and friction coefficient change curves of BNNS@Cu-(Ti) / Cu and BNNS / Cu composite materials after high-temperature hot working deformation at 1000°C in Example 3 and Comparative Example 3. DETAILED DESCRIPTION
[0042] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.
[0043] In the following embodiments:
[0044] The purity of BNNS powder is 99.9%, the number of layers is 5 to 20, the thickness is 5nm to 20nm, and the sheet diameter is 100nm to 200nm. Zhejiang Yamei Nanotechnology Co., Ltd.
[0045] CuAc·H2O, NaOH, and glucose were all analytical grade (AR ≥ 99%) and were obtained from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0046] The purity of Cu powder is 99.9%, the particle size is 20μm to 50μm, and the morphology can be spherical, flake, or any irregular shape. Shanghai Naio Nano Technology Co., Ltd.
[0047] The purity of nano-Ti powder is 99.9%, the morphology is spherical, and the particle size is 100nm-200nm, Shanghai Naio Nano Technology Co., Ltd.
[0048] Scanning electron microscope: Nova Nano-450, FEI, USA;
[0049] Transmission electron microscope: SA 58000x, FEI, USA;
[0050] Mechanical properties of the BNNS@Cu-(Ti) / Cu and BNNS / Cu composites prepared in the examples and comparative examples were characterized by using a universal tensile testing machine (AUTOGRAPH AG-I, Shimadzu Corporation, Japan) for tensile tests at room temperature. The sample size (dog bone type) was 16 mm × 2 mm × 1.5 mm (length × width × thickness); the tensile rate was 0.2 mm / min.
[0051] Friction and wear properties of the BNNS@Cu-(Ti) / Cu and BNNS / Cu composites prepared in the examples and comparative examples were characterized as follows: Friction tests were conducted at room temperature using a friction and wear tester (MS-M9000, Lanzhou, China), where the test load was 10N to 15N and the rotation speed was 100r / min to 150r / min.
[0052] Example 1
[0053] A method for preparing a novel high-strength and high-wear-resistant boron nitride reinforced copper-based composite material, the specific steps are as follows:
[0054] (1) Preparation of BNNS@Cu composite reinforcement
[0055] 0.3g BNNS powder and 15g hydrated copper acetate (CuAc·H2O) were weighed and ultrasonically dispersed in deionized water for 10min respectively. The BNNS dispersion solution was added to the CuAc·H2O solution and stirred in a 60℃ water bath for 30min to obtain a BNNS / CuAc mixed solution. Subsequently, 9g sodium hydroxide (0.5mol / L) and 7g glucose (0.8mol / L) were weighed and dispersed into a solution and added in sequence. When the color of the solution changed from dark blue to brick red, stirring was stopped, and BNNS / CuO powder was obtained by filtration and vacuum drying. Finally, the above powder was reduced at 300℃ for 200min in a vacuum tube furnace with Ar / H2 as protective reducing gas to obtain BNNS@Cu composite reinforcement powder.
[0056] (2) Preparation of BNNS@Cu-(Ti) composite powder
[0057] The BNNS@Cu powder obtained in step (1) and 1 g of nano-Ti powder were mixed in a ball mill, and alcohol accounting for about 1 / 4 of the volume of the ball mill was added. Argon was used as a protective gas, and the ball mill was milled for 120 min at a speed of 200 r / min (ball-to-material ratio of 10:1). The powder was vacuum dried to obtain a BNNS@Cu-(Ti) composite powder having a morphology as shown in FIG. Figure 1 shown.
[0058] (3) Preparation of BNNS@Cu-(Ti) / Cu composite bulk
[0059] 30 g of Cu powder was weighed and melted into a Cu melt in a vacuum induction melting furnace at 1100 °C (heating rate: 50 °C / min), and the BNNS@Cu-(Ti) composite powder obtained in step (2) was added. The furnace was evacuated to a vacuum (5 × 10 -4 Pa, Ar is the protective gas), continue to melt at 1100 ° C, and repeat the melting for 3 to 5 times (stirring / turning the sample 3 to 5 times) until it is evenly mixed to ensure that the sample is completely melted to the bottom of the mold. After keeping warm for 5 minutes, turn off the vacuum and the instrument. After the melt solidifies and the cavity cools to room temperature (about 20 minutes), take out the sample to obtain a BNNS@Cu-(Ti) / Cu composite block.
[0060] (4) Thermal deformation
[0061] The BNNS@Cu-(Ti) / Cu composite block obtained in step (3) is subjected to heat deformation treatment at 800°C using a hot working deformation device (hot rolling mill), wherein the hot rolling is performed for three passes, with a pressing depth of 1.5 mm in each pass, a rolling deformation of 25%, and a total rolling deformation of 75%.
[0062] EPMA surface scanning analysis was performed on the samples after thermal deformation, and the results are as follows: Figure 2 shown.
[0063] In order to verify the diffusion of titanium during hot working deformation, EPMA surface scanning was performed on the typical BNNS area of the composite material after hot rolling at 800℃. The element distribution is shown in Figure 2 (cf). Figure 2 The distribution of N elements in (c) shows that this area is a typical BNNS area, where B is a light element and cannot be identified by EPMA. Figure 2 As shown in (e), a large amount of Ti element enrichment was observed in this area, and the surrounding Ti concentration was low (such as area A and area B), indicating that Ti diffused into the BNNS area after heat treatment. Therefore, the heat treatment results show that the Ti element in the Cu matrix continuously migrates to the surface of BNNS and enriches to form an interfacial transition layer. This result better explains the formation mechanism of the transition layer of the BNNS@Cu-(Ti) / Cu composite material, and also shows that before reaching the Ti-B transition phase formation temperature, high temperature provides a driving force for diffusion, and the copper matrix provides a path for the effective diffusion of Ti into BNNS.
[0064] Comparative Example 1
[0065] (1) Weigh 30 g of Cu powder and add it into a vacuum induction melting furnace. Vacuum the furnace to 5 × 10 -4 Pa (with Ar as protective gas), and smelted into a molten state at a temperature of 1100°C (heating rate: 50°C / min) to obtain a Cu melt.
[0066] (2) Weigh 0.3 g of BNNS powder and add it to the Cu melt obtained in step (1). Evacuate the furnace to a vacuum (5 × 10 - 4 Pa, Ar is the protective gas), and the smelting is continued at 1100 °C until it is uniformly mixed. After keeping warm for 5 minutes, the vacuum is turned off, the instrument is turned off, and the sample is taken out after the melt solidifies and the cavity cools to room temperature to obtain a BNNS / Cu composite block.
[0067] (3) The BNNS / Cu composite block obtained in step (2) is subjected to a hot deformation treatment at 800° C. using a hot working deformation device (hot rolling mill), wherein the hot rolling is performed for 3 passes, the pressing amount for each pass is 1.5 mm, the rolling deformation amount is 25%, and the total rolling deformation amount is 75%.
[0068] Known, ρ (BNNS) ≈2.25g / cm 3 <ρ (Cu) ≈8.9g / cm 3 ; Through calculation, we know that ρ (BNNS-Cu-(1wt%Ti)) ≈8.85g / cm 3 ≈ρ (Cu) ≈8.9g / cm 3 ;
[0069] If BNNS powder is added directly to the Cu melt, the BNNS powder will inevitably suspend, stratify or agglomerate. This result will cause uneven dispersion of BNNS in the Cu matrix, reduce the wettability between the two, easily cause interface debonding, and reduce the interface bonding strength. Therefore, the BNNS / Cu composite powder is prepared in advance by the MLM method, that is, BNNS is added to the molten Cu matrix in the form of a high-density composite powder, avoiding the stratification problem caused by density differences, and achieving uniform dispersion of BNNS in the Cu matrix, such as step (1) in the embodiment.
[0070] The conductivity and hardness of the composite materials prepared in Example 1 and Comparative Example 1 were tested. The results are as follows: Figure 3 As shown; the mechanical properties and friction and wear performance tests (10N, 100r / min), the results are as follows Figure 4 As shown (the friction coefficient curve is the curve after smoothing the points).
[0071] like Figure 3 As shown, the composite material obtained by the molecular level mixing method combined with the vacuum melting process and reasonable hot working deformation treatment (800°C) has better performance. Comparing Example 1 and Comparative Example 1, the composite material of Example 1 still maintains good electrical conductivity (about 91% IACS). As for hardness, the composite material of Example 1 has a significant improvement over the composite material of Comparative Example 1, from 108.5HV to 143.6HV, an increase of about 32.4%. The main reasons for this phenomenon are: on the one hand, Example 1 obtains uniformly dispersed BNNS by the MLM method, and the resulting composite material organization is more uniform than Comparative Example 1; on the other hand, in Example 1, TiB is generated by in-situ interface reaction. x The transition layer interface improves the interface bonding between BNNS and copper substrate. However, the control group did not use the MLM method and did not perform microalloying on the copper substrate, resulting in lower performance than Example 1.
[0072] like Figure 4As shown, after hot working deformation at 800°C, the tensile strength of the composite material of Example 1 is significantly improved compared with that of the composite material of Comparative Example 1, reaching about 400MPa, an increase of about 35%. This is mainly attributed to the fact that after the addition of the Ti alloy element, an interface reaction occurs with the BNNS to generate a uniform transition layer, which can effectively improve the interface wettability between the BNNS and the copper matrix, thereby improving the interface bonding strength, and the strengthening effect of the reinforcement is significantly improved. For the friction coefficient, the composite material of Example 1 is reduced to 0.55 (the comparative example is 0.8), a decrease of about 36%. This is mainly attributed to the fact that a lubricating film is formed on the surface of the block during the sliding process, and the ceramic particles (TiB x ) can stabilize the lubricating layer, avoid interference from other factors during the sliding process, effectively reduce the plastic deformation of the composite material, and thus improve its wear resistance. In comparative example 1, there are a large number of agglomerates, resulting in many defects, which is not conducive to the self-lubricating effect of BNNS.
[0073] Example 2
[0074] A method for preparing a novel high-strength and high-wear-resistant boron nitride reinforced copper-based composite material, the specific steps are as follows:
[0075] (1) Preparation of BNNS@Cu composite reinforcement
[0076] 3g BNNS powder and 150g hydrated copper acetate (CuAc·H2O) were weighed and ultrasonically dispersed in deionized water for 20min, and the BNNS dispersion solution was added to the CuAc·H2O solution and stirred in a water bath at 80℃ for 60min to obtain a BNNS / CuAc mixed solution. Subsequently, 90g sodium hydroxide (0.5mol / L) and 70g glucose (0.8mol / L) were weighed and dispersed into a solution and added in sequence. When the color of the solution changed from dark blue to brick red, stirring was stopped, and BNNS / CuO powder was obtained by filtration and vacuum drying. Finally, the above powder was reduced at 400℃ for 300min in a vacuum tube furnace with Ar / H2 as protective reducing gas to obtain BNNS@Cu composite reinforcement powder.
[0077] (2) Preparation of BNNS@Cu-(Ti) composite powder
[0078] The BNNS@Cu powder obtained in step (1) and 10 g of nano-Ti powder were mixed in a ball mill, and alcohol accounting for about 1 / 3 of the volume of the ball mill was added. Argon was used as a protective gas, and the mixture was ball milled at a speed of 250 r / min for 180 min (ball-to-material ratio of 15:1). The powder was then vacuum dried to obtain a BNNS@Cu-(Ti) composite powder.
[0079] (3) Preparation of BNNS@Cu-(Ti) / Cu composite bulk
[0080] 300 g of Cu powder was weighed and melted into a Cu melt at 1300 °C (heating rate: 100 °C / min) in a vacuum induction melting furnace. The BNNS@Cu-(Ti) composite powder obtained in step (2) was added and the furnace was evacuated to a vacuum (5 × 10 -3 Pa, Ar is the protective gas), continue to melt at 1300 ° C, and repeat the melting for 3 to 5 times (stirring / turning over 3 to 5 times) until evenly mixed to ensure that the sample is completely melted to the bottom of the mold. After keeping warm for 10 minutes, turn off the vacuum and the instrument. After the melt solidifies and the cavity cools to room temperature (about 20 minutes), take out the sample to obtain a BNNS@Cu-(Ti) / Cu composite block.
[0081] (4) Thermal deformation
[0082] The BNNS@Cu-(Ti) / Cu composite block obtained in step (3) is subjected to heat deformation treatment at a temperature of 1000°C using a hot working deformation device (hot rolling mill), wherein the hot rolling is performed for 5 passes, each pass has a pressing amount of 1 mm, a rolling deformation amount of 15%, and a total rolling deformation amount of 75%.
[0083] Comparative Example 2
[0084] (1) Weigh 300g Cu powder and add it into the vacuum induction melting furnace. Vacuum it to 5×10 -3 Pa (with Ar as protective gas), and smelted into a molten state at a temperature of 1300°C (heating rate: 100°C / min) to obtain a Cu melt.
[0085] (2) Weigh 3 g of BNNS powder and add it to the Cu melt obtained in step (1). Evacuate the furnace to a vacuum (5 × 10 - 3 Pa, Ar is the protective gas), and the smelting is continued at 1300 ° C until it is evenly mixed. After keeping warm for 10 min, the vacuum is turned off, the instrument is turned off, and the sample is taken out after the melt solidifies and the cavity cools to room temperature to obtain a BNNS / Cu composite block.
[0086] (3) The BNNS / Cu composite block obtained in step (2) is subjected to a hot deformation treatment at a temperature of 1000° C. using a hot working deformation device (hot rolling mill), wherein the hot rolling is performed for 5 passes, the pressing amount for each pass is 1 mm, the rolling deformation amount is 15%, and the total rolling deformation amount is 75%.
[0087] The conductivity and hardness of the composite materials prepared in Example 2 and Comparative Example 2 were tested. The results are as follows: Figure 5 As shown; the mechanical properties and friction and wear performance tests (15N, 150r / min), the results are as follows Figure 6As shown (the friction coefficient curve is the curve after smoothing the points).
[0088] like Figure 5 As shown, the composite material obtained by the molecular level mixing method combined with the vacuum melting process and reasonable heat treatment deformation treatment has better performance as in Example 1. After heat treatment deformation, the conductivity of the composite material of Example 2 is slightly higher than that after heat treatment deformation at 800°C. This is mainly due to the higher temperature heat treatment, which makes the Ti element almost completely precipitate from the matrix and diffuse to the BNNS to react with the interface, reducing the Ti solid solution while also reducing the copper lattice distortion, which plays a role in reducing the scattering during electron transmission. However, excessive Ti (3wt%) diffuses to the BNNS to react with the interface, generating an uneven transition layer, which is more likely to cause debonding at the interface between the BNNS and the matrix, which is also the reason for the decrease in its hardness.
[0089] like Figure 6 As shown, after thermal processing at 1000°C, the tensile strength and friction coefficient of the composite material of Example 2 are enhanced to a certain extent compared with the composite material of Comparative Example 2, but the effect is not significant. The enhancement mechanism is basically the same as that in Example 1.
[0090] Example 3
[0091] A method for preparing a novel high-strength and high-wear-resistant boron nitride reinforced copper-based composite material, the specific steps are as follows:
[0092] (1) Preparation of BNNS@Cu composite reinforcement
[0093] 1.5g BNNS powder and 70g hydrated copper acetate (CuAc·H2O) were weighed and ultrasonically dispersed in deionized water for 15min respectively. The BNNS dispersion solution was added to the CuAc·H2O solution and stirred in a 70℃ water bath for 45min to obtain a BNNS / CuAc mixed solution. Subsequently, 45g sodium hydroxide (0.5mol / L) and 35g glucose (0.8mol / L) were weighed and dispersed into a solution and added in sequence. When the color of the solution changed from dark blue to brick red, stirring was stopped, and BNNS / CuO powder was obtained by filtration and vacuum drying. Finally, the above powder was reduced at 350℃ for 250min in a vacuum tube furnace with Ar / H2 as protective reducing gas to obtain BNNS@Cu composite reinforcement powder.
[0094] (2) Preparation of BNNS@Cu-(Ti) composite powder
[0095] The BNNS@Cu powder obtained in step (1) and 5 g of nano-Ti powder were mixed in a ball mill, and alcohol accounting for about 1 / 3 of the volume of the ball mill was added. Argon was used as a protective gas, and the mixture was ball milled at a speed of 230 r / min for 150 min (ball-to-material ratio of 13:1). The powder was then vacuum dried to obtain a BNNS@Cu-(Ti) composite powder.
[0096] (3) Preparation of BNNS@Cu-(Ti) / Cu composite bulk
[0097] 160 g of Cu powder was weighed and melted into a Cu melt at 1200 °C (heating rate: 75 °C / min) in a vacuum induction melting furnace. The BNNS@Cu-(Ti) composite powder obtained in step (2) was added and the furnace was evacuated to a vacuum (5 × 10 -3 Pa, Ar is the protective gas), and the smelting is continued at 1200 °C. The smelting is repeated 4 times (stirring / turning the sample 4 times) until it is evenly mixed to ensure that the sample is completely melted to the bottom of the mold. After keeping warm for 8 minutes, the vacuum is turned off, the instrument is turned off, and the sample is taken out after the melt solidifies and the cavity cools to room temperature (about 20 minutes) to obtain a BNNS@Cu-(Ti) / Cu composite block.
[0098] (4) Thermal deformation
[0099] The BNNS@Cu-(Ti) / Cu composite block obtained in step (3) is subjected to heat deformation treatment at 900°C using a hot working deformation device (hot rolling mill), wherein the hot rolling is performed in four passes, with a pressing depth of 2 mm in each pass, a rolling deformation of 30%, and a total rolling deformation of 90%.
[0100] (1) Weigh 300g Cu powder and add it into the vacuum induction melting furnace. Vacuum it to 5×10 -3 Pa (with Ar as protective gas), and smelted into a molten state at a temperature of 1300°C (heating rate: 100°C / min) to obtain a Cu melt.
[0101] (2) Weigh 3 g of BNNS powder and add it to the Cu melt obtained in step (1). Evacuate the furnace to a vacuum (5 × 10 - 3 Pa, Ar is the protective gas), and the smelting is continued at 1300 ° C until it is evenly mixed. After keeping warm for 10 min, the vacuum is turned off, the instrument is turned off, and the sample is taken out after the melt solidifies and the cavity cools to room temperature to obtain a BNNS / Cu composite block.
[0102] (3) The BNNS / Cu composite block obtained in step (2) is subjected to a hot deformation treatment at 800° C. using a hot working deformation device (hot rolling mill), wherein the hot rolling is performed for 5 passes, the pressing amount for each pass is 1 mm, the rolling deformation amount is 15%, and the total rolling deformation amount is 75%.
[0103] Comparative Example 3
[0104] (1) Weigh 160 g of Cu powder and add it into a vacuum induction melting furnace. Vacuum the furnace to 5 × 10 -3 Pa (with Ar as protective gas), and smelted into a molten state at a temperature of 1200°C (heating rate: 75°C / min) to obtain a Cu melt.
[0105] (2) Weigh 1.5 g of BNNS powder and add it to the Cu melt obtained in step (1). Evacuate the furnace to a vacuum (5 × 10 - 3 Pa, Ar is the protective gas), and the smelting is continued at 1200 °C until it is evenly mixed. After keeping the temperature for 8 minutes, the vacuum is turned off, the instrument is turned off, and the sample is taken out after the melt solidifies and the cavity cools to room temperature to obtain a BNNS / Cu composite block.
[0106] (3) The BNNS / Cu composite block obtained in step (2) is subjected to a hot deformation treatment at a temperature of 900° C. using a hot processing deformation device (hot rolling mill), wherein the hot rolling is performed in four passes, the pressing amount in each pass is 2 mm, the rolling deformation amount is 30%, and the total rolling deformation amount is 90%.
[0107] The conductivity and hardness of the composite materials prepared in Example 3 and Comparative Example 3 were tested. The results are as follows: Figure 7 As shown; the mechanical properties and friction and wear performance tests (15N, 150r / min), the results are as follows Figure 8 As shown (the friction coefficient curve is the curve after point smoothing). Its enhancement mechanism is basically the same as that in Example 1.
[0108] In summary, the present invention provides a method for preparing a novel high-strength and high-wear-resistant boron nitride reinforced copper-based composite material. The preparation method is simple, has a short experimental cycle and is highly practical. The obtained composite material has high strength and high wear resistance while still maintaining good electrical conductivity. The interface transition layer (TiB x ), improves the interface bonding between BNNS and copper matrix, and can effectively solve the problems in the background technology. The prepared copper-based composite material exhibits excellent mechanical properties and wear resistance, and provides technical guidance for the development of high-performance copper-based composite materials for application in the field of power electronic materials, especially for use as brush materials, pantograph slide materials, electrical contact materials, conductive materials and friction materials.
[0109] The embodiments described above are only preferred embodiments of the present invention, rather than all embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art through any modification, replacement, improvement, etc. without any innovation are within the protection scope of the present invention.
Claims
1. A method for preparing a high-strength and high-wear-resistant boron nitride reinforced copper-based composite material, characterized in that: The method steps are as follows: (1) Preparation of BNNS@Cu composite reinforcement 0.3 g to 3 g of boron nitride nanosheet powder, namely BNNS powder, and 15 g to 150 g of hydrated copper acetate, namely CuAc∙H2O, were weighed and ultrasonically dispersed in deionized water for 10 min to 20 min respectively, and the BNNS dispersion solution was added to the CuAc∙H2O solution, and stirred in a water bath environment at 60°C to 80°C for 30 min to 60 min to obtain a BNNS / CuAc mixed solution; subsequently, 9 g to 90 g of sodium hydroxide and 7 g to 70 g of glucose were weighed and dispersed into a solution and then added in sequence, and BNNS / CuO powder was obtained by filtration and vacuum drying; finally, the above BNNS / CuO powder was reduced in a vacuum tube furnace with Ar / H2 as a protective reducing gas to obtain a BNNS@Cu composite reinforcement powder; (2) Preparation of BNNS@Cu-(Ti) composite powder The BNNS@Cu powder obtained in step (1) and 1 g to 10 g of nano-Ti powder are mixed in a ball mill, and alcohol is added, with argon as the protective gas. After ball milling, the powder is vacuum dried to obtain BNNS@Cu-(Ti) composite powder; (3) Preparation of BNNS@Cu-(Ti) / Cu composite bulk Weigh 30 g to 300 g of Cu powder and melt it into a Cu melt in a vacuum induction melting furnace, add the BNNS@Cu-(Ti) composite powder obtained in step (2), evacuate the furnace to vacuum, repeatedly melt for several times until uniformly mixed, keep warm, turn off the vacuum, turn off the instrument, and take out the sample after the melt solidifies and the cavity cools to room temperature to obtain a BNNS@Cu-(Ti) / Cu composite block; (4) Thermal deformation The BNNS@Cu-(Ti) / Cu composite block obtained in step (3) is subjected to heat deformation treatment in a high temperature environment using a heat processing deformation device to obtain a BNNS@Cu-(Ti) / Cu composite material.
2. The method for preparing a high-strength and high-wear-resistant boron nitride reinforced copper-based composite material according to claim 1, characterized in that: In step (1), the BNNS is a single-layer, double-layer or multi-layer boron nitride nanosheet; the CuAc∙H2O, NaOH and glucose are all analytically pure, with AR≥99%.
3. The method for preparing a high-strength and high-wear-resistant boron nitride reinforced copper-based composite material according to claim 1, characterized in that: In step (1), the BNNS powder has a flake diameter of 100 nm to 200 nm and an added content of 0.1 wt% to 0.3 wt%.
4. The method for preparing a high-strength and high-wear-resistant boron nitride reinforced copper-based composite material according to claim 1, characterized in that: In step (1), the vacuum reduction heating rate is 5°C / min~10°C / min; the insulation temperature is 300°C~400°C; and the insulation time is 200 min~300 min.
5. The method for preparing a high-strength and high-wear-resistant boron nitride reinforced copper-based composite material according to claim 1, characterized in that: In step (2), the particle size of the nano-Ti powder is 100 nm to 200 nm, and the morphology is spherical; the added content is 1 wt% to 3 wt%.
6. The method for preparing a high-strength and high-wear-resistant boron nitride reinforced copper-based composite material according to claim 1, characterized in that: In step (2), the amount of alcohol added is 1 / 4 to 1 / 3 of the volume of the ball mill; the ball-to-material ratio is 10:1 to 15:1; the ball milling time is 120 min to 180 min; and the ball milling speed is 200 r / min to 250 r / min.
7. The method for preparing a high-strength and high-wear-resistant boron nitride reinforced copper-based composite material according to claim 1, characterized in that: In step (3), the Cu powder has a particle size of 20 μm to 50 μm and a spherical or flaky shape.
8. The method for preparing a high-strength and high-wear-resistant boron nitride reinforced copper-based composite material according to claim 1, characterized in that: In step (3), the initial vacuum degree of the vacuum induction furnace is: 5×10 -4 ~10 -3 Pa; heating rate: 50℃ / min~100℃ / min; melting temperature: 1100℃~1300℃; holding time: 5 min~10 min; melting 3~5 times.
9. The method for preparing a high-strength and high-wear-resistant boron nitride reinforced copper-based composite material according to claim 1, characterized in that: In step (4), the hot rolling temperature is 800°C to 1000°C; the hot rolling is performed for 3 to 5 passes, the pressing amount for each pass is ≤2 mm, the rolling deformation is ≤30%, and the total rolling deformation is ≤90%.
10. The method for preparing a high-strength and high-wear-resistant boron nitride reinforced copper-based composite material according to claim 1, characterized in that: In step (3), the Cu powder morphology is any irregular shape.
Citation Information
Patent Citations
Diamond heat-conducting composite material and preparation method thereof
CN103966533A
Preparation method of modified silicon carbide and boron nitride electronic packaging material
CN106832785A